The endochondral bone protein CHM1 sustains an undifferentiated, invasive phenotype, promoting lung metastasis in Ewing sarcoma. Issue 9 (21st August 2017) - von Heyking, Kristina; Calzada‐Wack, Julia; Göllner, Stefanie; Neff, Frauke; Schmidt, Oxana; Hensel, Tim; Schirmer, David; Fasan, Annette; Esposito, Irene; Müller‐Tidow, Carsten; Sorensen, Poul H.; Burdach, Stefan; et al.
Abstract : Ewing sarcomas (ES) are highly malignant, osteolytic bone or soft tissue tumors, which are characterized by EWS–ETS translocations and early metastasis to lung and bone. In this study, we investigated the role of the BRICHOS chaperone domain‐containing endochondral bone protein chondromodulin I (CHM1) in ES pathogenesis. CHM1 is significantly overexpressed in ES, and chromosome immunoprecipitation (ChIP) data demonstrate CHM1 to be directly bound by an EWS–ETS translocation, EWS‐FLI1. Using RNA interference, we observed that CHM1 promoted chondrogenic differentiation capacity of ES cells but decreased the expression of osteolytic genes such as HIF1A, IL6, JAG1, and VEGF . This was in line with the induction of the number of tartrate‐resistant acid phosphatase (TRAP + )‐stained osteoclasts in an orthotopic model of local tumor growth after CHM1 knockdown, indicating that CHM1‐mediated inhibition of osteomimicry might play a role in homing, colonization, and invasion into bone tissues. We further demonstrate that CHM1 enhanced the invasive potential of ES cells in vitro . This invasiveness was in part mediated via CHM1‐regulated matrix metallopeptidase 9 expression and correlated with the observation that, in an xenograft mouse model, CHM1 was essential for the establishment of lung metastases. This finding is in line with the observed increase in CHM1 expression in patient specimens with ES lung metastases. Our results suggest that CHM1 seems to have pleiotropic functions in ES, which need to be further investigated, but appears to be essential for the invasive and metastatic capacities of ES. Abstract : The endochondral bone protein CHM1 is regulated by the Ewing sarcoma (ES) chimeric transcription factor, EWS‐FLI1. In samples of lung metastases from patients with ES, CHM1 expression is clearly enhanced. CHM1 maintains an undifferentiated chondrocytic phenotype and promotes invasiveness and metastasis in ES.